2020
DOI: 10.1103/physreva.101.023620
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-induced topological bound states and Thouless pumping in a one-dimensional optical lattice

Abstract: We study topological features of interacting spin-1 2 particles in one-dimensional state-dependent optical lattices. Due to the co-translational symmetry, we introduce the center-of-mass Zak phase with the help of center-of-mass momentum. There appear topological bound states composed by two particles in different spin states via tuning hopping and interaction strengths. Under symmetric open boundary conditions, topological edge bound-states appear as a result of the non-trivial center-ofmass Zak phase of boun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…For an infinite structure, the total energy is invariant if spatial positions of the two excitations are shifted by a unit cell as a whole. It means that the center-of-mass momentum is a good quantum number according to the many-body Bloch theorem [36][37][38][39]. To present the Hamiltonian in a blockdiagonal form with different momenta, we introduce a new basis…”
Section: Band Structure and The Chern Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…For an infinite structure, the total energy is invariant if spatial positions of the two excitations are shifted by a unit cell as a whole. It means that the center-of-mass momentum is a good quantum number according to the many-body Bloch theorem [36][37][38][39]. To present the Hamiltonian in a blockdiagonal form with different momenta, we introduce a new basis…”
Section: Band Structure and The Chern Numbermentioning
confidence: 99%
“…By arranging the positions of qubits and designing the waveguide structure, the topological edge states have been analyzed in singleexcitation systems [30][31][32][33]. However, exotic effects may emerge in interacting topological systems when two or more particles (or quasiparticle excitations) interact [34][35][36][37][38][39]. Being analytically and numerically more challenging, the study of an interplay between photon interaction, non-Hermiticity, and topology is an exciting novel avenue to be explored in this field.…”
Section: Introductionmentioning
confidence: 99%
“…5 could be instead simulated by using state dependent lattices in a similar fashion as proposed in Ref. [62]. One species would experience a lattice positioned on the blue sites with hopping J 1 whereas the other species would experience a different lattice positions on the red sites with hopping J 2 .…”
Section: Discussionmentioning
confidence: 99%
“…While preparing this manuscript, we became aware of a recent work [62] investigating topological bound states on a triangular ladder with nearest-neighbor interactions, as realized in state-dependent lattices. Besides, another recent study [73] has shown how fractional corner charges appear in the ground state of a 2D SSH lattice with Bose-Hubbard interactions.…”
Section: Discussionmentioning
confidence: 99%
“…These two-body states, which are stable even for repulsive interactions due to the finite bandwidth of the singleparticle kinetic energy [9], have been observed [10][11][12][13] and extensively analyzed [14][15][16][17][18][19][20][21][22][23][24][25] in optical lattices, and have also been emulated in photonic systems [26,27] and in topolectrical circuits [28]. Motivated in part by these advances, several recent works have focused on the topological properties of two-body states [13,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], with the long-term aim of paving the path to a better comprehension of topological phases in a full many-body interacting scenario. A distinctive advantage that these small-sized systems offer is that it is often possible to map the problem of two interacting particles in a lattice into a single-particle model defined in a different lattice, the topological characterization of which can then be performed with well-established techniques [31][32][33]36,40,…”
Section: Introductionmentioning
confidence: 99%